Assessment of the determinants of agricultural greenhouse gas emissions in selected Organisation for Economic Co-operation and Development countries within the framework of the environmental Kuznets curve hypothesis - Seyranlioglu, Onur; Cilek, Arif; Yaman, Serdar; Gursoy, Samet; Erdem, Azad; Barut, Abdulkadir (Wiley, 2025)
BACKGROUNDThis study examines the relationship between agricultural greenhouse gas (GHG) emissions, economic growth (EG), and financial development (FD) within the framework of the environmental Kuznets curve (EKC) hypothesis in Organisation for Economic Co-operation and Development (OECD) countries. Using data from 2000 to 2020, the panel data analysis evaluates variables including EG, FD, foreign direct investment (FDI), agricultural energy consumption (EC), population (POP), agricultural land (LAND), and environmental policy stringency (EPS).RESULTSLong-run elasticity estimates obtained using bias-adjusted ordinary least squares (BA-OLS) demonstrate an inverted U-shaped relationship between EG, FD, and GHG emissions. A panel Fisher test reveals causal patterns among the variables. The findings indicate that EG and FD initially increased GHG emissions by boosting investments in the agricultural sector but emissions declined once a certain income or development level was reached, supporting the EKC hypothesis. Stricter environmental policies were found to be effective in reducing emissions. Population growth was also found to reduce emissions by enhancing agricultural productivity, and the expansion of LAND increased emissions. One of the important findings of the study is that the interactions between environmental policies, EG, and FD can reduce GHG emissions significantly.CONCLUSIONThe study emphasizes the need to adopt sustainable EG strategies, tightening environmental policies, and promoting sustainable agricultural technologies in OECD countries. Sharing agricultural sustainability and low-carbon development strategies through knowledge and technology transfer among OECD countries is recommended to combat global climate change effectively. In conclusion, coordinated efforts by OECD countries are required in order to enhance low-carbon agricultural development. (c) 2025 Society of Chemical Industry.
Keywords: agricultural greenhouse gas emissions; environmental Kuznets curve; financial development and economic growth; sustainable agricultural technologies